2005
DOI: 10.1080/17450390500148071
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age of growing turkeys on digesta viscosity and nutrient digestibility of maize, wheat, barley and oats fed as such or with enzyme supplementation

Abstract: The effects of age of growing turkeys and beta-glucanase-xylanase activity-containing feed enzyme supplementation on digestibility and feeding value of pelleted maize, wheat, barley and oats were investigated in growing turkeys using excreta collection and ileal sampling by slaughter. Excreta were collected and turkeys were slaughtered at 4, 8 and 12 weeks of age. Viscosity of jejuno-duodenal digesta, caecal volatile fatty acid concentration, ileal crude protein digestibility, total tract fat digestibility and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
4
5
0
Order By: Relevance
“…There is association between extent of digesta-viscosity reduction and improvement in protein digestibility (Palander et al, 2005). Many others have also reported improvement in N (Yang et al, 2010) and amino acid digestibility (Boguhn and Rodehutscord, 2010) in response to carbohydrase supplementation.…”
Section: Carbohydrasesmentioning
confidence: 94%
“…There is association between extent of digesta-viscosity reduction and improvement in protein digestibility (Palander et al, 2005). Many others have also reported improvement in N (Yang et al, 2010) and amino acid digestibility (Boguhn and Rodehutscord, 2010) in response to carbohydrase supplementation.…”
Section: Carbohydrasesmentioning
confidence: 94%
“…The current study also observed decreased d0-21 LWG and FCR when the NC was supplemented with an NSPase. This is in agreement with Barrios and coauthors [48]. While these authors found that the addition of NSPase can improve growth performance of broilers fed a cornsoybean meal based diet, it was also noted that when dietary treatments were reduced in energy and protein, the NSPase was unable to compensate, and feed efficiency decreased.…”
Section: Resultssupporting
confidence: 89%
“…Wheat utilized in the PC_2, NC and AC1 diets was ground using a roller mill. All diets were fed in mash form and particle size was determined using a Ro-Tap Particle Size Analyzer [48] ( Table 3). Complete feed samples for each treatment were collected post-enzyme addition for proximate analysis and β-glucanase activity ( Table 3).…”
Section: Feed Manufacture and Diet Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the effect of enzymes on feed or dietary energy may be related to the amount of substrate available to the enzyme, availability of energy from the ingredient itself, or both (Adeola and Cowieson, 2011). According to Palander et al (2005), the improvement in energy from cereal grains with carbohydrase supplementation can be masked when the energy value of the cereal grain is high. Similarly, in the study of Adeola et al (2008), the carbohydrate improved ME in diets with reduced energy, but not in diets with higher ME.…”
Section: Discussionmentioning
confidence: 99%